The Role of NRF2 in Bone Metabolism – Friend or Foe? - Han, Jie; Yang, Kuan; An, Jinyang; Jiang, Na; Fu, Songbo; Tang, Xulei (Frontiers in Endocrinology, 2022)
Bone metabolism is closely related to oxidative stress. As one of the core regulatory factors of oxidative stress, NRF2 itself and its regulation of oxidative stress are both involved in bone metabolism. NRF2 plays an important and controversial role in the regulation of bone homeostasis in osteoblasts, osteoclasts and other bone cells. The role of NRF2 in bone is complex and affected by several factors, such as its expression levels, age, sex, the presence of various physiological and pathological conditions, as well as its interaction with certains transcription factors that maintain the normal physiological function of the bone tissue. The properties of NRF2 agonists have protective effects on the survival of osteogenic cells, including osteoblasts, osteocytes and stem cells. Activation of NRF2 directly inhibits osteoclast differentiation by resisting oxidative stress. The effects of NRF2 inhibition and hyperactivation on animal skeleton are still controversial, the majority of the studies suggest that the presence of NRF2 is indispensable for the acquisition and maintenance of bone mass, as well as the protection of bone mass under various stress conditions. More studies show that hyperactivation of NRf2 may cause damage to bone formation, while moderate activation of NRF2 promotes increased bone mass. In addition, the effects of NRF2 on the bone phenotype are characterized by sexual dimorphism. The efficacy of NRF2-activated drugs for bone protection and maintenance has been verified in a large number of in vivo and in vitro studies. Additional research on the role of NRF2 in bone metabolism will provide novel targets for the etiology and treatment of osteoporosis.